Faktor-Faktor Yang Mempengaruhi Manajemen Laba Pada Perusahaan Manfaktur - Tita Andriyani, Ardiansyah, R (Jurnal Paradigma Akuntansi, 2019)
This research aims to determine the effect audit committee independence, audit committee activities, number of audit committee, and the institutional ownership toward the earning management. This research uses 58 samples manufacturing companies listed on the Indonesia Stock Exchange in the year of 2014-2016. Using Eviews program version 9. The results of T test indicate that audit committee activities and institutional ownership have a not significant effect on earning management and audit committee independence , and number of audit committee have a significant effect on earning management. The results of this research indicate that all independent variables simultaneously have a significant effect on firm value (F test).